(3fXe aUjM KYdHs - (3eGdc Hf YHO GdQMef GdeUehOi GdeGdbi GHf GdeQMds; (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3MeO GdEdg hGLH dPGJg hTcQg Ydi YdGgHGJg fMeOg SHMGfg hfTcQg hYf PfhH SdaJ fSJZaQI s
(3BNQgG (B:s
(3gPH ajgG bhdg hhWCg dCLd PG dbHgG GdehWCI hGSeY dg hGOY dg HGdQMeI jG fGXQkG ajgG QRbJ GdYUeg s
(3HgG JBcd ef CWQGagGs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GddZIs